NILAI PRAGMATIS MASYARAKAT PAPUA DALAM TRADISI LISAN INSOS DAN KONAYO - Insum Malawat; H Hengki; A Akhiruddin (ppjbsip, 2022)
The title of this research is Papuan’s Pragmatic value in folklore Insos and Konayo. It is based on some factors, those are preservation effort to protect Papuan Folklore that becomes marginalized, to protect the identity of the owner, to protect culture treasure of the nation, to preserve it to be a local wisdom media. This research aims to describe Papuan’s ideology that contains pragmatics value in verbal prose Insos and Konayo. This is a content analysis of qualitative research. Verbal folklore and literature pragmatics are theories used in this research. Based on the result of the analysis concluded that the Papuan keep tightly their traditions. Those traditions contain massage and promises from their ancestors. The traditions contain sacral values that ties their society in customary law, natural law, and social law. Verbal tradition preservation reflects love feeling and thanksgiving to their ancestors. The pragmatic value that contains in Insos and Konayo is education value that shows the obedience to the customary law. The function of education value in both of the stories is to become a self-introspection tool. Breaking a customary law can risk themself or can risk the lawbreaker rule. Customary low preservation is the key to create peace and balance life in the world.